Using Large Scale Summative Tests to Advance the Integration of Sustainable Development Competencies: A Model for Test Construction - Williams-McBean Clavia T. (Discourse and Communication for Sustainable Education)
There is an urgent need for global citizens to develop sustainable development competencies (SDCs) if our world is to survive threats to its development and sustainability. These competencies can be developed through education for sustainable development (ESD). However, implementing ESD is challenged by teachers’ and students’ prioritisation of the assessed curriculum while ESD remains largely unassessed in the education sector. The knowledge, skills, values and attitudes reflected in tests and assessments, especially large-scale, standardised, summative tests, influence classroom practices considerably. This paper proposes that the integration of SDCs can be accelerated by constructing large-scale tests to measure these competencies, thereby capitalising on the influence of the tests. It presents a model for constructing these tests and provides ways in which the format of multiple choice and extended written response items may be optimised to measure SDCs.